WEB-BASED SPATIAL INFORMATION SYSTEM TO SUPPORT COLLABORATIVE LAHARS DISASTER MANAGEMENT - Jumadi Jumadi; R. Suharyadi; Arbind M. Tuladhar (Faculty of Geography, Universitas Gadjah Mada, 2012)
After the 2010 eruption of Merapi, some areas at Sleman Regency experienced with laharsdisaster. Many agencies have their own responsibility to overcome the problems incollaborative work. Nevertheless, it is lack of spatial/GIS data support on their decisionmaking as well as on their communications. The main objective of this research was todevelop spatial information system to support collaborative lahars disaster managementespecially for response and recovery phase of the impact on infrastructures at SlemanRegency. Questionnaires and semi-structured interviews were used to investigate their needof the spatial data and the data availability. Basically respondents agreed that spatial datais important in their communication and decision making support. Specifically, theapplication is utilized with specific spatial analysis tools to support decision makingprocesses. The users’ evaluation of the prototype resulted that almost all of respondents givea good mark to the system.